Remote Electrical Neuromodulation (REN) Relieves Acute Migraine: A Randomized, Double‐Blind, Placebo‐Controlled, Multicenter Trial. Issue 8 (9th May 2019) - Yarnitsky, David; Dodick, David W.; Grosberg, Brian M.; Burstein, Rami; Ironi, Alon; Harris, Dagan; Lin, Tamar; Silberstein, Stephen D.
Abstract : Objective: To assess the efficacy and safety of a remote electrical neuromodulation (REN) device for the acute treatment of migraine. Background: There is a significant unmet need for novel effective well‐tolerated acute migraine treatments. REN is a novel acute migraine treatment that stimulates upper arm peripheral nerves to induce conditioned pain modulation – an endogenous analgesic mechanism in which conditioning stimulation inhibits pain in remote body regions. A recent pilot study showed that REN can significantly reduce headache. We have conducted a randomized, double‐blind, sham‐controlled study to further evaluate the efficacy and safety of REN for the acute treatment of migraine. Methods: This was a randomized, double‐blind, sham‐controlled, multicenter study conducted at 7 sites in the United States and 5 sites in Israel. Two hundred and fifty‐two adults meeting the International Classification of Headache Disorders criteria for migraine with 2‐8 migraine headaches per month were randomized in a 1:1 ratio to active or sham stimulation. A smartphone‐controlled wireless device was applied for 30‐45 minutes on the upper arm within 1 hour of attack onset; electrical stimulation was at a perceptible but non‐painful intensity level. Migraine pain levels were recorded at baseline, 2, and 48 hours post‐treatment. Most bothersome symptoms (MBS) were also recorded. The primary efficacy endpoint was the proportion of participants achieving pain relief at 2 hours post‐treatment (improvement from severe or moderate pain to mild or none, or from mild pain to none). Relief of MBS and pain‐free at 2 hours were key secondary endpoints. Results: Active stimulation was more effective than sham stimulation in achieving pain relief (66.7% [66/99] vs 38.8% [40/103]; therapeutic gain of 27.9% [CI95%, 15.6‐40.2]; P < .0001), pain‐free (37.4% vs 18.4%, P = .003), and MBS relief (46.3% vs 22.2%, P = .0008) at 2 hours post‐treatment. The pain relief and pain‐free superiority of the active treatment was sustained 48 hours post‐treatment. The incidence of device‐related adverse events was low and similar between treatment groups (4.8% [6/126] vs 2.4% [3/126], P = .499). Conclusions: REN provides superior clinically meaningful relief of migraine pain and MBS compared to placebo, offering a safe and effective non‐pharmacological alternative for acute migraine treatment.